Determination of Academic Stress and Coping Mechanism among Adolescence during Pandemic Covid-19: An Indian Perspective - Nagle, Y. K.; Sharma, Usha (Issues and Development in Health Research Vol. 7, 2021)
The present chapter aimed at focusing on conceptual understanding and insight into the function of academic stress in association with psychological factors. The COVID-19 has further supplemented more academic stress on adolescents; parental pressure and their expectation which has led them to take radical steps like suicide attempt, committing suicide and majority of them are suffering with depression and anxiety. Various researches have supported the same and reported that alarming rate has been noted of the children who are unable to cope up with the stressors faced by them in academics and unable to fulfill the parental expectations. Also, the pandemic has become one of the precursors to the same by not providing the adolescents with enough space and cope up with the demands of school and parents. These issues require immediate attention and focus; hence the present chapter focuses on academic stress and coping mechanism among Adolescents during pandemic Covid-19 in Indian perspective. In order to overcome such venerable affects faced by the youth the possible measures and recommendation to provide the child with healthy and fruitful environment and for parents are suggested in the chapter.